Landscape and Place: a study on the Integration Terminals O Manaus/AM - Brito, Miguel Sá de Souza (Revista Verde Grande: Geografia e Interdisciplinaridade, 2023)
This research has its main landmark the establishment of the relationship between the subjects and the daily production in the Integration Terminals of public transport in the city of Manaus. For this, we sought to answer the following questions: In which contexts the Integration Terminals are no longer a place of passage and become a Landscape of Fear for users of public transport in Manaus? How did the COVID-19 pandemic change the way users produce the Terminal space? and; Do Integration Terminal workers conceive of this space in the same way as transport users and/or passersby? For this, two methodological procedures were designed/organized, the first of which was based on the survey of references that would enable the strengthening of the bases for it. The second methodological procedure for the construction of this research was the field work/research with the objective of interviewing and identifying the profiles of the subjects who use the integration terminals in Manaus. Based on a phenomenologically based Geography, this research seeks to go beyond the researcher’s vision, turning to the “look” of the researched subject and his/her life experience.